Students' Perception of Using Google Classroom in The Paragraph Writing Class at English Education Department - Ridwan, Nur Marwinda; Muhsin, Muh. Arief; Mahmudah, Dzur Rif’ah (Journal of Computer Interaction in Education, 2022)
This study aims to determine the perception of each student in using Google Classroom in the second semester paragraph writing course at the Department of English Education, Unismuh Makassar. In this study used quantitative research method. The data was collected through distributing questionnaires to each student. The sampling technique used by the researchers in this study was purposive sampling. The sample in this study were 27 students consisting of 14 students from class BG2A and 13 students from class BG2B class 2021 majoring in English Education. The results of this study was showed the variable that achieves the highest index was the "Ease for Use" variable, which was 80,9%, means that students agree that Google Classroom very easy to use during the learning process of paragraph writing, while the variable with the lowest index was “active”, which was 74,8%, means that it was still a little students who are active in the learning process using Google Classroom. However, the results of the analysis show that the index for each variable was in the "Agree" category. So in this study it can be concluded that students have a positive perception on using Google Classroom in paragraph writing courses.